EDUCATOR INNOVATION IN STIMULATING SELF-EFFICACY AND CREATIVITY IN LEARNING MATHEMATICS STUDENTS BASED ON X MIND (MIND MAPPING) IN MI - Hasanah, Fadilah; Ubaidillah, Ubaidillah; Umam, Khotibul (STIT AL MULTAZAM, 2023)
Over time, technological advances and changes in the learning paradigm require educators to be more creative and innovative. Patently one of the subjects that is a challenge for students is learning mathematics. Mathematics is often perceived as a difficult and boring subject by most learners so to overcome these problems, technology-based mathematics learning innovations need to be internalised. This study aims to analyse the self-efficacy and learning creativity of students in learning mathematics through innovative mathematics learning media based on X Mind at Madrasah Ibtidaiyah Sumber Bunga Kapongan Situbondo, especially in class IV. This research uses a qualitative approach using a descriptive qualitative approach. The subjects in this study were grade IV homeroom teachers, mathematics teachers and grade IV students. Data acquisition through participatory observation, interviews with educators, and document analysis as a conclusion. The results showed that educator innovation in the form of X Mind-based mathematics learning media produced by students significantly, illustrating the formation of high self-efficacy, learning creativity, new imagination, understanding of mathematical concepts of KPK and FPB material, in producing innovative and active learning so as to support the achievement of learning objectives as expected.